Solid-state battery electrolyte membrane, preparation method and solid-state battery
By adjusting the binder content of the solid-state battery electrolyte membrane and using an extrusion coating method, the problem of cracks in the solid-state battery lamination process is solved, the stability and safety of the battery are improved, and the service life is extended.
Patent Information
- Application Number
- CN202411346978.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2024-12-27
AI Technical Summary
During the isostatic pressure recombination of solid-state batteries, the electrolyte membrane is cracked or broken due to the difference in thickness between the Overhang area and the laminate area, resulting in short circuit abnormalities and affecting electrochemical performance.
By adjusting the adhesive content in different areas of the electrolyte membrane, the adhesive content in the protruding area is greater than the corresponding area of the positive electrode, and the flexibility of the electrolyte membrane is improved. The electrolyte slurry is applied on the substrate by extrusion coating method, and the electrolyte slurry is controlled Film thickness and size enhance the pressure resistance of the electrolyte membrane.
It effectively reduces the short-circuit rate of solid-state battery cells, improves cycle stability and safety, extends the service life of the battery, and improves the application convenience of the electrolyte membrane.
Smart Images

Figure CN119208715A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of composite materials, and in particular to a solid-state battery electrolyte membrane, a preparation method and a solid-state battery. Background Art
[0002] With the rapid development of new energy vehicles, the existing liquid lithium battery product technology cannot meet the market demand, so the development of solid-state batteries has become the research and development focus of engineers. The electrolyte in liquid lithium batteries has the characteristics of high chemical reaction activity, easy oxidation, and easy combustion. Solid-state batteries use solid electrolytes instead of electrolytes to avoid the risk of liquid leakage. In addition, since the chemical activity of solid electrolytes is relatively stable and is less affected by ambient temperature, they are more stable in collisions and extrusions, and can be compatible with positive and negative electrode materials with higher specific capacity. Therefore, solid-state batteries are expected to open up room for battery energy density, further increase the range of electric vehicles, and achieve another upgrade of lithium battery technology.
[0003] At the same time, the research and development of solid-state batteries also faces huge challenges. Because solid-state batteries use a laminated isostatic pressing composite process, and the negative electrode and electrolyte membrane need to be overhanging to avoid short-circuiting between the positive and negative electrodes, there is a significant thickness difference between the overhang area and the laminated area during the composite process. After isostatic pressing, the high pressure will cause cracks or fractures in the overhang area of the electrolyte membrane; and the battery volume expansion during the charge and discharge cycle will also cause fractures in the overhang area, resulting in short-circuit anomalies in the assembled battery cell, which seriously affects the electrochemical performance of the battery cell. Summary of the invention
[0004] In view of the above problems of the prior art, the present application provides a solid-state battery electrolyte membrane, a preparation method and a solid-state battery. By adjusting the binder content of the electrolyte slurry, the flexibility of different regions of the electrolyte membrane is improved, and the short circuit rate of the finished battery cell is effectively reduced. The specific technical solution is as follows:
[0005] On the one hand, the present application provides a solid-state battery electrolyte membrane, characterized in that it includes a protruding area and a positive electrode corresponding area, the content of the adhesive in the protruding area is greater than the content of the binder in the positive electrode corresponding area, the positive electrode corresponding area refers to the part corresponding to the overlap of the solid-state battery electrolyte membrane and the positive electrode layer, and the protruding area refers to the part of the solid-state battery electrolyte membrane that exceeds the positive electrode layer.
[0006] In a possible implementation manner, the positive electrode corresponding region includes a first binder and a first electrolyte material, and a mass ratio of the first binder to the first electrolyte material is 1:9-99.
[0007] In a possible implementation manner, the protruding region includes a second binder and a second electrolyte material, and a mass ratio of the second binder to the second electrolyte material is 1:9-99.
[0008] In a possible implementation, the solid-state battery electrolyte membrane according to any one of claims 1 to 3 is characterized in that the solid-state battery electrolyte membrane satisfies at least one of the following characteristics:
[0009] The first binder includes one or more of hydrogenated styrene-butadiene block copolymer, styrene-butadiene block copolymer, polystyrene, polytetrafluoroethylene, polyvinylidene fluoride, styrene-butadiene rubber, polyacrylate, polyacrylonitrile, polyethylene oxide, and polyisobutylene;
[0010] The second binder includes one or more of hydrogenated styrene-butadiene block copolymer, styrene-butadiene block copolymer, polystyrene, polytetrafluoroethylene, polyvinylidene fluoride, styrene-butadiene rubber, polyacrylate, polyacrylonitrile, polyethylene oxide, and polyisobutylene;
[0011] The first electrolyte material includes at least one of an argyrodite-type sulfide electrolyte and a ThioLI SION-type sulfide electrolyte;
[0012] The second electrolyte material includes at least one of an argyrodite-type sulfide electrolyte, a ThioLISON-type sulfide electrolyte, and a single crystal halide electrolyte.
[0013] On the other hand, the present application provides a method for preparing a solid-state battery electrolyte membrane, characterized in that the preparation method comprises:
[0014] Providing a first electrolyte slurry and a second electrolyte slurry, wherein the mass proportion of the binder in the first electrolyte slurry is lower than the mass proportion of the binder in the second electrolyte slurry;
[0015] The first electrolyte slurry and the second electrolyte slurry are coated on a substrate, with the coating area of the second electrolyte slurry being located on the peripheral side of the coating area of the first electrolyte slurry, and dried to obtain a solid-state battery electrolyte membrane.
[0016] In a possible implementation manner, the preparation method satisfies at least one of the following characteristics:
[0017] The solid content of the first electrolyte slurry is 20% to 60%;
[0018] The solid content of the second electrolyte slurry is 20% to 60%.
[0019] In a possible implementation, the first electrolyte slurry and the second electrolyte slurry are simultaneously coated on the substrate by an extrusion coating method.
[0020] In a possible implementation manner, the drying treatment temperature is 90-220°C.
[0021] On the other hand, the present application provides a solid-state battery, comprising the aforementioned solid-state battery electrolyte membrane.
[0022] In a possible implementation, the solid-state battery further includes a negative electrode layer and a positive electrode layer, the negative electrode layer is consistent in size with the solid-state battery electrolyte membrane, and the positive electrode layer is smaller in size than the negative electrode layer.
[0023] Based on the above technical solution, this application has the following beneficial effects:
[0024] In the present application, by changing the binder content in different areas of the electrolyte membrane, without changing the ionic conductivity of the corresponding area of the positive electrode of the solid-state battery electrolyte membrane, the part of the solid-state battery electrolyte membrane that exceeds the positive electrode layer has better flexibility, and the ability of the solid-state battery electrolyte membrane to resist strong stress is improved, so that the solid-state battery electrolyte membrane can withstand the pressure in the static pressing process such as battery assembly, and can withstand the mechanical stress generated between the electrode and the electrolyte due to the volume expansion of the electrode during the charging and discharging process of the solid-state battery, thereby avoiding cracks or fractures in the overhang area due to stress, thereby preventing the battery cell from short-circuiting due to failure of the overhang area, and at the same time improving the cycle stability and safety of the solid-state battery containing the electrolyte membrane, and extending the service life of the solid-state battery; and, using the extrusion coating method, the two electrolyte slurries can be coated on the substrate at the same time, and the thickness of the prepared electrolyte membrane is uniform and controllable. The size of the electrolyte membrane can be controlled by changing the size of the gasket of the extrusion coater, thereby improving the convenience of application of the electrolyte membrane in solid-state batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the technical solutions and advantages in the embodiments of the present application or the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0026] Figure 1 : A schematic diagram of the structure of a solid-state battery electrolyte membrane provided in an embodiment of the present application;
[0027] Figure 2 : A schematic diagram of a cross-sectional structure of a solid-state battery provided in an embodiment of the present application;
[0028] Wherein, the accompanying drawings are marked as follows:
[0029] 1-solid-state battery electrolyte membrane, 11-positive electrode corresponding area, 12-protruding area, 2-negative electrode layer, 3-positive electrode layer. DETAILED DESCRIPTION
[0030] The technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0031] For the following defined terms, these definitions shall apply unless a different definition is given in the claims or elsewhere in this specification. All numerical values, whether or not explicitly indicated, are defined herein as modified by the term "about". The term "about" generally refers to a numerical range that a person of ordinary skill in the art considers to be equivalent to the stated values to produce substantially the same properties, functions, results, etc. A numerical range indicated by a lower value and a higher value is defined to include all numerical values included in the numerical range and all subranges included in the numerical range.
[0032] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions.
[0033] The term "overhang" in this application refers to the portion of the negative electrode layer and the electrolyte membrane that extends beyond the positive electrode layer.
[0034] The following describes a solid-state battery electrolyte membrane 1 provided in an embodiment of the present application. Figure 1 As shown, it includes a protruding area 12 and a positive electrode corresponding area 11, the content of the adhesive in the protruding area 12 is greater than the content of the adhesive in the positive electrode corresponding area 11, the positive electrode corresponding area 11 refers to the corresponding part where the solid-state battery electrolyte membrane overlaps the positive electrode layer, and the protruding area 12 refers to the part where the solid-state battery electrolyte membrane exceeds the positive electrode layer.
[0035] Based on the above scheme, since the protruding area 12 of the electrolyte membrane has a higher binder content, the protruding area 12 has better flexibility without affecting the ionic conductivity of the positive electrode corresponding area 11 of the electrolyte membrane; when the above-mentioned solid-state battery electrolyte membrane 1 is laminated and statically pressed with the negative electrode layer 2 and the positive electrode layer 3, the protruding area 12 of the electrolyte membrane can resist the high pressure stress, avoid cracks or fractures in the protruding area 12 of the electrolyte membrane, and thus avoid short circuit between the positive and negative electrodes; during the battery charge and discharge cycle, the volume expansion of the electrode will also cause mechanical stress between the electrode and the electrolyte membrane. The increased flexibility of the protruding area 12 of the electrolyte membrane can resist the stress, thereby improving the cycle stability and safety performance of the solid-state battery and extending the service life of the solid-state battery.
[0036] Specifically, the positive electrode corresponding region 11 includes a first binder and a first electrolyte material, and the mass ratio of the first binder to the first electrolyte material is 1:9 to 99; it can be understood that the mass ratio of the first binder to the first electrolyte is any point value in 1:9 to 99, and illustratively, the mass ratio of the first binder to the first electrolyte is 1:99, 1:89, 1:79, 1:69, etc., preferably 1:49 to 99. In this way, the mass ratio of the binder to the electrolyte material is controlled within the above range, and the flexibility of the electrolyte membrane can be increased without affecting the technology of the ionic conductivity of the electrolyte membrane. If the mass ratio of the binder to the electrolyte material is lower than 1:99, the binder cannot play the role of adhering the solid electrolyte material during the film forming process, resulting in low mechanical strength of the prepared electrolyte membrane; if the mass ratio of the binder to the electrolyte material is higher than 1:9, the excessively high binder content will result in low ionic conductivity of the electrolyte membrane, thereby affecting ionic conduction and adversely affecting the charge and discharge performance of the solid-state battery.
[0037] Specifically, the first binder includes at least one of hydrogenated styrene-butadiene block copolymer, styrene-butadiene block copolymer, polystyrene, polytetrafluoroethylene, polyvinylidene fluoride, styrene-butadiene rubber, polyacrylate, polyacrylonitrile, polyethylene oxide, and polyisobutylene, and has excellent heat resistance, compression deformation resistance, and mechanical properties, and is conducive to forming a stable film structure.
[0038] Specifically, the first electrolyte material includes at least one of an argyrodite-type sulfide solid electrolyte and a Thio-LISION-type sulfide solid electrolyte. The sulfide solid electrolyte has high ionic conductivity, helps to improve the charge and discharge rate of the solid-state battery, and shows good cycle stability.
[0039] Preferably, the argyrodite-type sulfide electrolyte includes Li 6 PS 5At least one of X, wherein X is selected from Cl, Br or I.
[0040] Preferably, the Thio-LISION type sulfide electrolyte comprises (100-x)Li 2 S-xP 2 S 5 , Li 4 -yA-yB y S 4 or Li 4 S N 4 At least one of , wherein 0<x<100, A is Ge or Si, B is one or more of P, Al or Zn, and 0<y<1; Preferably, the Thio-LISION type sulfide electrolyte also includes at least one of X-doped Thio-LIS ION type sulfide electrolytes, wherein X is at least one of I and Br.
[0041] Specifically, the protruding area 12 includes a second binder and a second electrolyte material, and the mass ratio of the second binder and the second electrolyte material is 1:9 to 99. It can be understood that the mass ratio of the first binder and the first electrolyte is any point value in the range of 1:9 to 99; illustratively, the mass ratio of the first binder and the first electrolyte can be 1:9, 1:19, 1:29, 1:39, etc.; preferably, the above mass ratio is 1:9 to 49; the mass ratio of the second binder and the second electrolyte material is controlled within the above range, so that the protruding area 12 of the electrolyte membrane has better flexibility without affecting the ionic conductivity of the electrolyte membrane, so as to resist the pressure borne during the isostatic pressing process, prevent the protruding area 12 of the electrolyte membrane from cracking or rupture, and thus avoid short circuit between the positive and negative electrodes.
[0042] Specifically, the second binder includes one or more of hydrogenated styrene-butadiene block copolymer, styrene-butadiene block copolymer, polystyrene, polytetrafluoroethylene, polyvinylidene fluoride, styrene-butadiene rubber, polyacrylate, polyacrylonitrile, polyethylene oxide, and polyisobutylene. Preferably, the second binder can be a hydrogenated styrene-butadiene block copolymer, which has excellent heat resistance, compression deformation resistance and mechanical properties, and is beneficial to improving the mechanical properties of the protruding area 12.
[0043] Specifically, the second electrolyte material includes at least one of an argyrodite-type sulfide solid electrolyte, a Thio-LISION-type sulfide solid electrolyte, and a single crystal halide electrolyte.
[0044] Preferably, the argyrodite-type sulfide solid electrolyte comprises Li 6 PS 5At least one of X, wherein X is selected from Cl, Br or I.
[0045] Preferably, the Thio-LIS ION type sulfide solid electrolyte comprises (100-x)Li 2 S-xP 2 S 5 , Li 4 -yA-yB y S 4 or Li 4 S N 4 At least one of, wherein 0<x<100, A is Ge or Si, B is one or more of P, Al or Zn, and 0<Y<1; Preferably, the Thio-LISION type sulfide electrolyte also includes at least one of X-doped Thio-LISION type sulfide electrolytes, wherein X is at least one of I and Br.
[0046] Preferably, the halide electrolyte comprises Li 3 AM 6 8H 2 At least one of O, wherein A is selected from one or more of In, Y, Yb, and Sc, and M is selected from one or more of F, Cl, and Br. Compared with sulfide solid electrolytes, halide electrolytes have good chemical stability. During the thermal runaway of the positive electrode, they can effectively block the adverse chain reaction of thermal runaway of the battery, reduce the risk caused by the chemical reaction, make the protruding area 12 conductive, and improve its chemical stability, thereby improving the safety performance of the solid-state battery.
[0047] Among them, the first electrolyte material and the second electrolyte material can be selected from the same type of material or different types of materials. Preferably, compared with the first electrolyte material, the second electrolyte material is selected to be a material with better chemical stability, so that the protruding area 12 of the electrolyte membrane maintains good stability during the battery charging and discharging process, thereby improving the safety performance of the solid-state battery.
[0048] The embodiment of the present application also provides a method for preparing a solid-state battery electrolyte membrane 1, by which the above-mentioned solid-state battery electrolyte membrane 1 is prepared. This specification provides the method operation steps as in the embodiment, but more or fewer operation steps may be included based on conventional or non-creative labor. The order of steps listed in the embodiment is only one way of executing the order of many steps and does not represent the only execution order. When the actual preparation method is executed, it can be executed in the order of the method shown in the embodiment or the accompanying drawings or in parallel. Specifically including the following steps:
[0049] S1. Prepare the first electrolyte slurry: add the first binder and the refined first electrolyte material into the solvent according to a proportion, stir and grind, and obtain the first electrolyte slurry.
[0050] Specifically, the solvent includes at least one of N-methylpyrrolidone, xylene, tetrahydrofuran, dodecane, trimethylbenzene or water, and the solvent can infiltrate the surface of the electrolyte material and swell the binder at room temperature to ensure the uniformity of dispersion of the components in the first electrolyte slurry, thereby improving the mixing uniformity of the electrolyte material and the binder, and facilitating subsequent stirring and grinding.
[0051] Specifically, the mass ratio of the first binder to the first electrolyte material is 1:9 to 99; it can be understood that the mass ratio of the first binder to the first electrolyte is any point value in the range of 1:9 to 99, which is not enumerated here; preferably, the above mass ratio is 1:49 to 99; in this way, the binder content of the first electrolyte slurry is controlled within the above range, and when the first electrolyte slurry is dried to form a film, the positive electrode corresponding area 11 of the electrolyte membrane can maintain good ionic conductivity.
[0052] S2. Prepare the second electrolyte slurry: add the second binder and the refined second electrolyte material into the solvent according to a proportion, stir and grind, and obtain the second electrolyte slurry.
[0053] Specifically, the mass ratio of the second binder and the second electrolyte material is 1:9 to 99, and the mass ratio of the second binder in the second electrolyte slurry is greater than the mass ratio of the first binder in the first electrolyte slurry; it can be understood that the mass ratio of the second binder and the second electrolyte is any point value in the range of 1:9 to 99, which is not enumerated here; preferably, the above mass ratio is 1:9 to 49. In this way, the mass ratio of the second binder and the second electrolyte material is controlled within the above range, so that the protruding area 12 of the solid-state battery electrolyte membrane has better flexibility than the positive electrode corresponding area 11, and does not affect the ionic conductivity of the positive electrode corresponding area 11, so that the protruding area 12 can resist the pressure borne during the isostatic pressing process of the electrode layer, prevent the protruding area 12 of the electrolyte membrane from cracking or rupture, thereby avoiding short circuit between the positive and negative electrodes, and improving the safety performance and cycle life of the solid-state battery.
[0054] Specifically, the solid content of the first electrolyte slurry is 20% to 60%. It can be understood that the solid content of the first electrolyte slurry is any point value between 20% and 60%. For example, the solid content in the first electrolyte slurry is 20%, 30%, 40%, etc. The solid content of the second electrolyte slurry is 20% to 60%. It can be understood that the solid content of the first electrolyte slurry is any point value between 20% and 60%, which is not enumerated here. In this way, controlling the solid content in the electrolyte slurry within the above range is conducive to the subsequent wet film formation of the electrolyte slurry. If the solid content is higher than the above range, it may cause the sedimentation of the solid electrolyte powder during coating, thereby affecting the uniformity of the membrane and the ionic conductivity of the electrolyte membrane; if the solid content is lower than the above range, it may be difficult to coat because the slurry fluidity is too high. Therefore, the solid content of the electrolyte slurry is within the above range, which is conducive to the subsequent coating to form an electrolyte membrane with uniform and controllable thickness.
[0055] S3. Apply the first electrolyte slurry and the second electrolyte slurry on a substrate, wherein the application area of the second electrolyte slurry is located on the periphery of the application area of the first electrolyte slurry, and dry the substrate to obtain a solid-state battery electrolyte membrane 1.
[0056] Specifically, the substrate includes at least one of steel foil, PET film, and aluminum foil, the thickness of the steel foil is 10-40 μm, the thickness of the PET film is 35-100 μm, the release force is 1-8 g, and the thickness of the aluminum foil is 13-17 μm. The above-mentioned substrate material has good chemical stability and can withstand various chemicals during wet coating, and the above-mentioned substrate material has good thermal stability and can withstand a certain range of temperatures during wet coating.
[0057] Specifically, the first electrolyte slurry and the second electrolyte slurry are simultaneously coated on the substrate by an extrusion coating method, and the coating area of the second electrolyte slurry is located on the peripheral side of the coating area of the first electrolyte slurry, so that the second electrolyte slurry with a higher binder content is located in the protruding area 12 of the electrolyte membrane after drying, so that the protruding area 12 can withstand high pressure during the isostatic pressing assembly of the battery, thereby avoiding cracks or ruptures in the protruding area 12.
[0058] Specifically, the extrusion coating method can simultaneously coat the first electrolyte material and the second electrolyte material at corresponding positions on the substrate. Compared with the extrusion coating of a single electrolyte slurry, the present application transforms the extrusion coater required for preparing the above-mentioned electrolyte membrane, transforms the inner cavity of the single coating die head into a main cavity and a sub-cavity, loads the first electrolyte slurry into the main cavity, and loads the second electrolyte material into the sub-cavity, and guides the gasket to extrude the two electrolyte slurries and evenly coat them on the substrate, and the second electrolyte slurry is coated on the peripheral side of the first electrolyte slurry.
[0059] In this way, the extrusion coater can be used to simultaneously coat the first electrolyte slurry and the second electrolyte slurry, so that the two slurries maintain uniform thickness during the coating process, and the interface area of the two parts of the electrolyte slurry is well fused, avoiding the process abnormality of metal leakage, thereby avoiding short circuit abnormalities in subsequent battery assembly. In addition, the extrusion coater can customize the gasket according to the size of the electrolyte membrane protruding area 12 and the positive electrode corresponding area 11 required for preparation, thereby realizing the preparation of electrolyte membranes of different sizes, and improving the convenience of application of the electrolyte membrane in solid-state batteries.
[0060] Specifically, the drying treatment temperature is 90-220°C; it can be understood that the drying treatment temperature can be any point value among the above temperatures; illustratively, the drying temperature is 90°C, 100°C, 110°C, etc.; in this way, the drying treatment temperature is controlled within the above temperature range, so that the solvent in the electrolyte slurry can be volatilized, and the solid material in the electrolyte slurry can be formed into a film on the substrate, and excessive temperature can be prevented from causing thermal degradation or structural damage of the electrolyte material and the binder, affecting their electrochemical properties and mechanical stability.
[0061] In this way, the solid-state battery electrolyte membrane 1 prepared by the above method has a higher binder content in the protruding area 12 than the corresponding area 11 of the positive electrode, so that the protruding area 12 has better flexibility; and the size and thickness of the solid-state battery electrolyte membrane 1 can be controlled by the extrusion coating method, which is beneficial to the application of the electrolyte membrane in solid-state batteries.
[0062] The present application also provides a solid-state battery. Figure 2 As shown, it includes the above-mentioned solid-state battery electrolyte membrane 1, and also includes a negative electrode layer 2 and a positive electrode layer 3.
[0063] Specifically, the negative electrode layer 2 includes a negative electrode material, a binder and a conductive agent, wherein the mass ratio of the negative electrode material, the binder and the conductive agent is 90-97:1-4:2-4; it can be understood that the mass ratio can be any point value in the range of 90-97:1-4:2-4, which is not enumerated here; wherein the binder includes at least one of polyvinylidene fluoride, carboxymethyl cellulose, hydrogenated styrene-butadiene block copolymer, polyacrylic acid, polyvinylidene chloride, styrene-butadiene-styrene block copolymer, and N-polyvinylidene fluoride-trifluoroethylene-2-acryloyl polycaprolactone; the solvent includes at least one of N-methylpyrrolidone, xylene, tetrahydrofuran, dodecane, trimethylbenzene and water; the conductive agent includes at least one of carbon black, multi-walled carbon nanotubes, and vapor-grown carbon fibers. The above-mentioned solid-state battery negative electrode layer based on pure silicon negative electrode has good interface compatibility. Silicon has thermodynamic stability to sulfide solid electrolyte, which can avoid chemical reaction between lithium metal and sulfide electrolyte, and the high working potential of silicon inhibits the formation of dendrites, thereby improving the safety and stability of the battery. At the same time, silicon has a high Young's modulus and can maintain dimensional stability under high pressure, which is conducive to retaining the negative electrode Overhang and avoiding cracks in the negative electrode Overhang during the subsequent isostatic pressing composite process.
[0064] Specifically, the positive electrode layer 3 includes a positive electrode active material, a sulfide electrolyte, a conductive agent and a binder, wherein the mass ratio of the positive electrode active material, the sulfide electrolyte, the conductive agent and the binder is 30-95: 5-60: 0-10: 0.1-10; it can be understood that the mass ratio can be any point value in 30-95: 5-60: 0-10: 0.1-10, which is not enumerated here; wherein the positive electrode material includes one or more of lithium cobalt oxide, lithium manganese oxide, nickel cobalt lithium manganese oxide, and lithium iron phosphate; the sulfide electrolyte includes argyrodite-type sulfide solid electrolyte Li i 6 PS 5 X, X is at least one of Cl, Br, I; the binder includes a fluorine-based copolymer containing tetrafluoroethylene monomer units, preferably at least one of polytetrafluoroethylene powder (PTFE), ethylene-tetrafluoroethylene copolymer (ETFE), and polyperfluoroethylene propylene (PFEP); the conductive agent includes at least one of carbon black, multi-walled carbon nanotubes, and vapor-grown carbon fibers. The above-mentioned solid-state battery positive electrode layer based on sulfide electrolyte has a higher capacity density and battery capacity than liquid lithium batteries. The conductive agent in the positive electrode layer can enhance the interface contact and stability between the positive electrode layer and the electrolyte membrane, which is beneficial to improving the cycle performance and rate performance of the battery.
[0065] Specifically, the solid-state battery electrolyte membrane 1 and the negative electrode layer 2 are stacked and isostatically pressed, and the solid-state battery electrolyte 1 membrane is transferred to the negative electrode layer 2 to obtain a negative electrode-electrolyte composite layer; the above-mentioned negative electrode-electrolyte composite layer is stacked with the positive electrode layer 3, so that the solid-state battery electrolyte membrane 1 is stacked between the positive electrode layer 3 and the negative electrode layer 2, and the solid-state battery is obtained after isostatic assembly. Among them, the negative electrode layer 2 is consistent with the size of the solid-state battery electrolyte membrane 1, and the size of the positive electrode layer 3 is smaller than the size of the negative electrode-electrolyte composite layer; in this way, the solid-state battery can retain the overhang area of the negative electrode layer 2 and the solid-state battery electrolyte membrane 1, ensuring that the negative electrode can accept lithium ions from the positive electrode, avoiding the precipitation of lithium ions on the surface of the negative electrode, thereby preventing the formation of lithium dendrites, and then preventing short circuits in the battery, and improving the safety performance of the battery.
[0066] The specific embodiments of the present application are introduced below in conjunction with the above technical scheme. The following examples describe the technical scheme of the present application in more detail, and these examples are only for illustrative purposes, because various modifications and changes within the scope of the disclosure of the present application are obvious to those skilled in the art. The reagents used in the examples can be obtained commercially or synthesized according to conventional methods, and can be used directly without further treatment, and the instruments and devices used in the examples can be obtained commercially.
[0067] Example 1
[0068] This embodiment provides a method for preparing a solid-state battery, which specifically includes the following steps:
[0069] Preparation of solid-state battery electrolyte membrane:
[0070] 1. Mix hydrogenated styrene-butadiene block copolymer (SEBS) binder and refined Li 6 PS 5 Cl electrolyte powder (LPSC) is mixed at a mass ratio of 1:99, a xylene solution is added after mixing, and ball milling is performed for 1 hour to obtain a first electrolyte slurry with a solid content of 20%-60%;
[0071] 2. Combine SEBS binder and refined Li 3 I nC 6 The electrolyte powder (LIC) is mixed in a mass ratio of 1:9, a xylene solution is added after mixing, and ball milling is performed for 1 hour to obtain a second electrolyte slurry with a solid content of 20%-60%;
[0072] 3. The first electrolyte slurry and the second electrolyte slurry are extrusion coated on a steel foil substrate at a baking temperature of 90-120° C. After the solvent is completely evaporated, an electrolyte membrane is obtained.
[0073] Preparation of positive electrode layer:
[0074] 1. The nickel-manganese-cobalt ternary material, LPSC, multi-walled carbon nanotubes and polytetrafluoroethylene powder are fully mixed in a powder grinder at a mass ratio of 85:15:5:5 to obtain a positive electrode mixed dry powder;
[0075] 2. Grind the positive electrode mixed dry powder thoroughly to fibrosis the polytetrafluoroethylene, and bond the mixed dry powder particles together to act as a binder to obtain a black viscous powder;
[0076] 3. The viscous powder is pressed at 90° C. to obtain a positive electrode layer.
[0077] Preparation of negative electrode layer:
[0078] 1. Add polyvinylidene fluoride-trifluoroethylene-2-acryloyl polycaprolactone (PVDF-HFP) binder into N-methylpyrrolidone (NMP) and stir magnetically for 4 hours to obtain PVDF-HFP-NMP glue;
[0079] 2. Mix micron silicon powder, carbon black and PVDF-HFP in a mass ratio of 96.5:1.5:2, and then add an appropriate amount of NMP to adjust the solid content to 45% to obtain a negative electrode mixed slurry;
[0080] 3. The above negative electrode mixed slurry was placed in a centrifugal mixer for dispersion, and the speed of the centrifugal mixer was set to 3000r / min for 15min to obtain pure silicon negative electrode slurry;
[0081] 4. The pure silicon negative electrode slurry is extrusion coated on a carbon-coated copper foil substrate at a baking temperature of 120-150°C to obtain a solid-state battery negative electrode layer.
[0082] Assembling solid-state batteries:
[0083] 1. Cut the solid-state battery electrolyte membrane and the negative electrode layer into pole pieces of the same size, align the solid-state battery electrolyte membrane with the negative electrode layer and perform isostatic transfer printing to obtain a negative electrode-electrolyte composite layer;
[0084] 2. Cut the positive electrode layer into a size smaller than the negative electrode-electrolyte composite layer, sandwich the negative electrode-electrolyte composite layer between the positive electrode layers, perform sandwich lamination, and then perform isostatic pressing at a pressure of 300 mPa, an oil temperature of 90°C, and a duration of 10 min to obtain an active assembly;
[0085] 3. After encapsulating the active assembly, a solid-state battery is obtained.
[0086] Example 2
[0087] The difference between this embodiment and embodiment 1 is that, in the process of preparing the solid-state battery electrolyte membrane, the SEBS binder and the refined L IC are mixed in a mass ratio of 1:19, and after mixing, a xylene solution is added, and the mixture is ball-milled for 1 hour to obtain a second electrolyte slurry with a solid content of 20%-60%; the rest is the same as embodiment 1.
[0088] Example 3
[0089] The difference between this embodiment and embodiment 1 is that, in the process of preparing the solid-state battery electrolyte membrane, the SEBS binder and the refined L IC are mixed in a mass ratio of 1:49, and after mixing, a xylene solution is added, and the mixture is ball-milled for 1 hour to obtain a second electrolyte slurry with a solid content of 20%-60%; the rest is the same as embodiment 1.
[0090] Example 4
[0091] The difference between this embodiment and embodiment 1 is that, in the process of preparing the solid-state battery electrolyte membrane, the SEBS binder and the refined LPSC are mixed in a mass ratio of 1:9, and after mixing, a xylene solution is added, and ball milling is performed for 1 hour to obtain a second electrolyte slurry with a solid content of 20%-60%; the rest is the same as embodiment 1.
[0092] Example 5
[0093] The difference between this embodiment and embodiment 1 is that, in the process of preparing the solid-state battery electrolyte membrane, the SEBS binder and the refined LPSC are mixed in a mass ratio of 1:19, and after mixing, a xylene solution is added, and the mixture is ball-milled for 1 hour to obtain a second electrolyte slurry with a solid content of 20%-60%; the rest is the same as embodiment 1.
[0094] Example 6
[0095] The difference between this embodiment and embodiment 1 is that, in the process of preparing the solid-state battery electrolyte membrane, the SEBS binder and the refined LPSC are mixed in a mass ratio of 1:49, and after mixing, a xylene solution is added, and the mixture is ball-milled for 1 hour to obtain a second electrolyte slurry with a solid content of 20%-60%; the rest is the same as embodiment 1.
[0096] Comparative Example 1
[0097] This comparative example provides a method for preparing a solid-state battery, which specifically includes the following steps:
[0098] Preparation of solid-state battery electrolyte membrane:
[0099] 1. Mix hydrogenated styrene-butadiene block copolymer (SEBS) binder and refined Li 6 PS 5Cl electrolyte powder (LPSC) was mixed at a mass ratio of 1:99, and a xylene solution was added after mixing, and ball milled for 1 h to obtain an electrolyte slurry with a solid content of 20%-60%;
[0100] 2. Mix the SEBS binder and the insulating ceramic powder in a mass ratio of 1:9, add the xylene solution after mixing, and ball mill for 1 hour to obtain an insulating ceramic slurry;
[0101] 3. The electrolyte slurry and insulating ceramic slurry are extrusion coated, and the coating substrate is a steel foil. The coating area of the insulating ceramic slurry is located on the periphery of the coating area of the electrolyte slurry. The baking temperature is 90-120°C. After the solvent is completely evaporated, an electrolyte membrane is obtained.
[0102] Furthermore, the electrolyte membrane obtained as described above is used to assemble a solid-state battery, and the specific steps and parameters used are consistent with those in the aforementioned embodiment 1, which will not be described in detail here.
[0103] Comparative Example 2
[0104] The difference between this embodiment and embodiment 1 is that, in the process of preparing the solid-state battery electrolyte membrane, the mass ratio of the SEBS binder and the refined LIC in the second electrolyte slurry is 1:99, which is the same as the mass ratio of the binder in the first electrolyte slurry; the remaining steps are the same as those in embodiment 1.
[0105] Comparative Example 3
[0106] The difference between this comparative example and Example 1 is that, in the process of preparing the solid-state battery electrolyte membrane, the mass ratio of the SEBS binder and the refined LPSC in the second electrolyte slurry is 1:99, which is the same as the mass ratio of the binder in the first electrolyte slurry; the remaining steps are the same as Example 1.
[0107] Comparative Example 4
[0108] The difference between this comparative example and Example 1 is that, in the process of preparing the solid-state battery electrolyte membrane, the mass ratio of the SEBS binder and the refined LPSC in the first electrolyte slurry is 1:9, which is the same as the mass ratio of the binder in the second electrolyte slurry; the remaining steps are the same as Example 1.
[0109] The above examples and comparative examples adopt the following test methods:
[0110] 1. Ionic conductivity test method:
[0111] The test frequency of the electrochemical workstation was set to 10 MHz-1000 Hz, the bias voltage was 0 V, and the Z′ value of the intersection of the straight line and the Z′ axis was taken as the total impedance R of the solid-state battery electrolyte membrane. The total ionic conductivity was calculated according to the conductivity calculation formula σ=L / (R*S), where L is the thickness of the sample, R is the total impedance, and S is the effective contact area between the sample and the electrode.
[0112] 2. Electrochemical performance test:
[0113] The solid-state battery was charged at a constant current and constant voltage of 0.1C to a voltage of 2.0-4.3V to test the discharge capacity of the sodium ion battery; the cyclic charge and discharge were repeated under the same conditions as above, and the discharge capacity of the battery after the 10th cycle was measured.
[0114] 3. Short circuit test:
[0115] Adjust the multimeter to the resistance range, and place the two test leads of the multimeter on the positive and negative poles of the assembled solid-state battery cell. If the multimeter displays "1", the cell is not short-circuited; if the multimeter displays a resistance value, the cell is short-circuited.
[0116] The solid-state batteries prepared in the above embodiments and the solid-state batteries prepared in the comparative examples were subjected to performance tests, and the test results are shown in the following table:
[0117] Table 1
[0118]
[0119] Table 2
[0120]
[0121] Table 3
[0122]
[0123] Referring to the test results in Table 1-3, combined with Examples 1-6, it can be seen that the electrolyte material in the protruding area in Examples 1-3 is LIC, and the electrolyte material in the protruding area in Examples 4-6 is LPSC. Comparing the two electrolyte materials, under the condition of the same binder content in the protruding area, when the electrolyte material in the protruding area is LIC, the ionic conductivity of the solid-state battery electrolyte membrane is low, but the solid-state battery including the electrolyte membrane has a low short circuit rate, and a high charge and discharge capacity, and has better cycle charge and discharge performance. This is because, compared with the LPSC electrolyte, the LIC electrolyte has a lower ionic conductivity, but the LIC electrolyte material can effectively block the inferior chain reaction of battery thermal runaway during the thermal runaway of the positive electrode, and work stably in the battery system, reducing the risk caused by chemical reactions; and the protruding area of the electrolyte membrane only provides less ionic conductivity transmission, so the protruding area can use a more stable electrolyte material to improve the safety performance of the battery cell.
[0124] Combining Example 1 with Comparative Example 1, it can be seen that when the protruding area is completely insulated, the protruding area does not provide a transmission path for lithium ions, resulting in obvious blocking of lithium ion transmission at the junction of the protruding area and the corresponding area of the positive electrode, thereby affecting the capacity of some battery cells. This further illustrates that when the protruding area contains electrolyte materials and binders, the flexibility of the protruding area can be improved without affecting the electrochemical properties of the corresponding area of the positive electrode.
[0125] Combining Examples 1-6 with Comparative Examples 2-3, it can be seen that under the same electrolyte system, the higher the binder content in the protruding area, the lower the short-circuit rate of the solid-state battery. When the binder content in the protruding area is lower than the set range, it may cause the protruding area of the electrolyte membrane to break or rupture, thereby causing the solid-state battery to short-circuit, affecting the safety and service life of the battery.
[0126] Combining Examples 1 and 4 with Comparative Example 4, it can be seen that when the binder content in the area corresponding to the positive electrode of the electrolyte membrane is too high, it will cause a significant decrease in the charge and discharge capacity, initial efficiency and cycle performance of the electrolyte membrane. The increase in the binder content in the electrolyte membrane will affect the transmission path of lithium ions, resulting in an increase in the migration path of lithium ions, and then increase the polarization internal resistance of the battery cell, resulting in a decrease in active lithium ions, causing a significant decrease in the electrochemical performance of the battery, and at the same time affecting the cycle performance.
[0127] To sum up, when the protruding area of the solid-state battery electrolyte membrane has a higher binder content than the corresponding area of the positive electrode, and the electrolyte material contained in the protruding area has better chemical stability, it can reduce the short-circuit rate of the battery without affecting the ionic conductivity of the corresponding area of the positive electrode, improve the cycle stability and safety performance of the solid-state battery, and extend the service life of the solid-state battery.
[0128] The above description has fully disclosed the specific implementation methods of the present application. It should be pointed out that any changes made by technicians familiar with the field to the specific implementation methods of the present application do not deviate from the scope of the claims of the present application. Accordingly, the scope of the claims of the present application is not limited to the above specific implementation methods.
Claims
1. A solid-state battery electrolyte membrane, characterized in that: It includes a positive electrode corresponding area and a protruding area, the content of the adhesive in the protruding area is greater than the content of the binder in the positive electrode corresponding area, the positive electrode corresponding area refers to the part corresponding to the overlap of the solid-state battery electrolyte membrane and the positive electrode layer, and the protruding area refers to the part of the solid-state battery electrolyte membrane that exceeds the positive electrode layer.
2. The solid-state battery electrolyte membrane according to claim 1, characterized in that: The positive electrode corresponding region includes a first binder and a first electrolyte material, and the mass ratio of the first binder to the first electrolyte material is 1:9-99.
3. The solid-state battery electrolyte membrane according to claim 1, characterized in that The protruding region includes a second binder and a second electrolyte material, and a mass ratio of the second binder to the second electrolyte material is 1:9-99.
4. The solid-state battery electrolyte membrane according to any one of claims 1 to 3, characterized in that The solid-state battery electrolyte membrane satisfies at least one of the following characteristics: The first binder includes one or more of hydrogenated styrene-butadiene block copolymer, styrene-butadiene block copolymer, polystyrene, polytetrafluoroethylene, polyvinylidene fluoride, styrene-butadiene rubber, polyacrylate, polyacrylonitrile, polyethylene oxide, and polyisobutylene; The second binder includes one or more of hydrogenated styrene-butadiene block copolymer, styrene-butadiene block copolymer, polystyrene, polytetrafluoroethylene, polyvinylidene fluoride, styrene-butadiene rubber, polyacrylate, polyacrylonitrile, polyethylene oxide, and polyisobutylene; The first electrolyte material includes at least one of an Argentum-type sulfide solid electrolyte and a Thio-LISION-type sulfide solid electrolyte; The second electrolyte material includes at least one of an Argentum-type sulfide solid electrolyte, a Thio-LISION-type sulfide solid electrolyte, and a single crystal halide electrolyte.
5. A method for preparing a solid-state battery electrolyte membrane, characterized in that: The preparation method comprises: Providing a first electrolyte slurry and a second electrolyte slurry, wherein the mass proportion of the binder in the first electrolyte slurry is lower than the mass proportion of the binder in the second electrolyte slurry; The first electrolyte slurry and the second electrolyte slurry are coated on a substrate, with the coating area of the second electrolyte slurry being located on the periphery of the coating area of the first electrolyte slurry, and dried to obtain a solid-state battery electrolyte membrane.
6. The preparation method according to claim 5, characterized in that: The preparation method meets at least one of the following characteristics: The solid content of the first electrolyte slurry is 20% to 60%; The solid content of the second electrolyte slurry is 20% to 60%.
7. The preparation method according to claim 5 or 6, characterized in that: The first electrolyte slurry and the second electrolyte slurry are simultaneously coated on the substrate by an extrusion coating method.
8. The preparation method according to claim 5 or 6, characterized in that: The drying treatment temperature is 90-220°C.
9. A solid-state battery, characterized in that: Comprising the solid-state battery electrolyte membrane as claimed in claim 1.
10. The solid-state battery according to claim 9, characterized in that: It also includes a negative electrode layer and a positive electrode layer. The negative electrode layer has the same size as the solid-state battery electrolyte membrane, and the positive electrode layer is smaller than the negative electrode layer.
Citation Information
Cited By
Electrolyte membrane as well as wet preparation method and application thereof
CN120511347A
Intelligent baking system for copper foil
CN121206854A
